Avaliação fisiológica e bioquímica da germinação de sementes de Myracrodruon Urundeuva Fr. All. (Anacardiaceae) sob diferentes condições abióticas - Virgens, Ivana Oliveira (2009)
The objective of this study was to evaluate the germinative behavior of M. urundeuva seeds exposed to different temperatures (termal screening), hydric potentials (hydric screening) and the combinations between them. Experiments were performed at the State University of Feira de Santana Germination Laboratory, in a completely randomized experimental design, with four replications of 50 seeds/treatment and in three stages. On stage I, seeds were placed in chambers at the temperatures from 20 to 40ºC, with intervals of 5ºC, then adjusting to the temperature of 50% of germination (T50) at 33ºC. On stage II, seeds were exposed to PEG 6000 solutions at different osmotic potentials (0,0 to -1,2 MPa), adjusting the potential of 50% of germination (􀀁50) in -0,7 MPa. On stage III, it was combined with T50 at different osmotic potentials (0,0; -0,2; -0,7 and -1,0 MPa) and the 􀀁50 at the temperatures of 25, 33 and 40°C. On the thermal screening, it was established 25ºC as great temperature, 33ºC as T50 and 40ºC as the stress temperature (no germination); on the hydric screening the potential of -1,0 MPa was considered the one which no longer allowed the seeds to germinate, bringing a stress to the Aroeira seeds (osmoprimed conditions); at - 0,7 MPa was considered as 􀀁50 (60%). On the combined stress just the treatment seeds germinated -0,2 MPa/33°C (12% only), showing that the combination between the two stresses significantly affected the physiologic behavior of the seeds and also that the combination between high temperatures and the reduction of the osmotic potentials reduces the germination of the M. urundeuva seeds.